Pengaruh Laba Akuntansi, Arus Kas Operasi dan Return On Equity (ROE) Terhadap Return Saham Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi yang Terdaftar di Bursa Efek Indonesia Periode 2015-2017 - Setia, Monika; Purwanto, Nanang; Setiyowati, Supami Wahyu (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2018)
This study aims to determine the effect both simultaneously and partially between accounting profit, operating cash flow, and Return On Equity (ROE) on stock returns of manufacturing companies in the consumer goods industry sector. The data collection method uses the documentation method. This research was conducted at the manufacturing companies in the consumer goods industry sector in the 2015-2017 period. The data used in this study are secondary data in the form of financial statements and company stock price information. The research data were obtained from the Investment Gallery of Kanjuruhan University Malang and www.idx.co.id. Sampling technique uses purpose sampling which is based on certain criteria so 19 companies are used as research samples. The analysis technique used is multiple linear regression analysis. The results of this study indicate that simultaneous accounting profit, operating cash flow and Return On Equity affect stock returns. Partially accounting profit, operating cash flow and Return On Equity affect stock returns. The higher accounting profit, operating cash flow and return on equity (ROE), the higher the return received by investors. Conversely the smaller accounting profit, operating cash flow and Return On Equity (ROE), the smaller the return that investors will receive.